Emission reduction with hybrid mechanisms in civil aviation: An evolutionary game approach - Zhang, Peiwen; Ding, Rui; Wang, Yu; Zhang, Qiaoyan; Zhao, Lianzheng (Frontiers in Environmental Science, 2023)
This paper proposes a hybrid carbon emission reduction mechanism, including major airlines in the emission trading systems and implementing carbon tax for small and medium-sized airlines. First, a tripartite evolutionary game model is constructed to study strategic behaviors. Second, four scenarios of evolutionarily stable strategies (ESSs) are analyzed. Finally, the influencing parameters of players’ strategy choices are analyzed through simulations. The results show that: (1) the steady development scenarios (1, 1, 1) can be reached under the appropriate conditions; (2) the parameters such as carbon allowances and carbon tax prices significantly influence the evolutionary trend of stakeholders’ dynamic choices; (3) the implementation of a hybrid mechanism by the government could facilitate the choice of low carbon operation strategies for both types of airlines. Accordingly, a series of policy recommendations are proposed to promote carbon emission reduction in civil aviation.